PENDUGAAN BIAYA POKOK PRODUKSI DAN PENDAPATAN USAHATANI JAGUNG DI KECAMATAN ADILUWIH KABUPATEN PRINGSEWU - Rizkia Fortuna Utami; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The objectives of this study are to analyze the standard cost and the income of corn farming in Adiluwih District, Pringsewu Regency. Respondents are corn farmers chosen by using simple random sampling method.  Data were collected by interviewing the respondents on the corn farming in the Rainy Season (RS) 2016/2017 and the Dry Season (DS) 2017. The data were analyzed by using the economic and financial analysis. The average corn productivities were 2.84 ton/ha in RS 2016/2017 and 2.75 ton/ha in DS 2017. The average standard costs for producing corn was IDR2,927/kg and its 95% confidence interval was IDR2,168/kg – IDR3,686/kg.  The average net income over its cash costs was IDR5.73 million/ha, the same amount in RS 2016/2017 and in DS 2017.  The net income over its total cost was IDR3.57 million/ha in RS 2016/2017 and also in DS 2017 Key words: confidence interval, corn, income, standard cost